2018
DOI: 10.1057/s41267-018-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

The international penetration of ibusiness firms: Network effects, liabilities of outsidership and country clout

Abstract: The burgeoning of ibusiness firms in the modern digital economy challenges the received internationalization theory. Given that ibusinesses such as social networking sites create value by providing a digital platform for users to interact with one another, we employ a user-network perspective and externalization logic, suggesting that ibusinesses' internationalization process depends critically on users' collective interactions, instead of being solely driven by firms' market commitments as noted by the Uppsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(208 citation statements)
references
References 125 publications
(189 reference statements)
5
147
1
2
Order By: Relevance
“…As in any high-tech industry, platform quality is likely to be a function of firm-specific technological capabilities, which can help firms claim market leadership (McIntyre, 2011;Sheremata, 2004). IB research confirms that platform quality is positively associated with the likelihood of penetration in foreign markets (Chen et al, 2019).…”
Section: Internalization Theory and Digital Commercementioning
confidence: 52%
See 1 more Smart Citation
“…As in any high-tech industry, platform quality is likely to be a function of firm-specific technological capabilities, which can help firms claim market leadership (McIntyre, 2011;Sheremata, 2004). IB research confirms that platform quality is positively associated with the likelihood of penetration in foreign markets (Chen et al, 2019).…”
Section: Internalization Theory and Digital Commercementioning
confidence: 52%
“…Since the Internet can in many cases substantially reduce the cost of deploying FSAs across national borders, many digital firms may be characterized as Born Globals (Hennart, 2014), although some scholars specify that the internationalization of digital firms is constrained by reliance on locally embedded complementary resources (Verbeke, Coeurderoy, & Matt, 2018). Recent IB research demonstrates that platforms offer important opportunities for extending theory (Banalieva & Dhanaraj, 2019); scholars contend that the internationalization of digital firms may be beyond the scope of firm-centric logic, being driven more by user interaction than by unilateral firm commitment (Brouthers, Geisser, & Rothlauf, 2016;Chen, Shaheer, Yi, & Li, 2019;Coviello, Kano, & Liesch, 2017;Shaheer & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The findings by Chen et al (2019) are very relevant for our analysis for two reasons. First, they show that international spread is not just a matter of global network effects: national barriers still hold for digital businesses.…”
Section: Characteristics Of Transacted Itemsmentioning
confidence: 94%
“…That is, being on the market or on the web is not enough -meeting customers' needs is essential for international growth; it lends support to the development of online reputations. But the main research findings concern the role of international networks and the influence of specific countries, labelled "country clout" (Chen et al, 2019). It was found that the global installed base only "exerts a trivial effect on the likelihood of penetration in new target countries" (Chen et al, 2019, p. 184).…”
Section: Characteristics Of Transacted Itemsmentioning
confidence: 99%
See 1 more Smart Citation